EFFECT OF USING SOME FEED ADDITIVES IN THE FATTENING RATIONS OF SHARABI CALVES ON SOME GROWTH AND CARCASS CHARACTERISTICS - A. Nasser (Mesopotamia Journal of Agriculture)
This study was conducted on Al-Rasheida station farms,Mosul using 12 sharabi local calves at age(10-12months)and weights (183.33 ± 40.66kg.)were assigned randomly into three group, and these groups were fed ad libitum on ration consisted barley,wheat barn,soy bean meal and yellow corn(control ration),first group fed in control ration only(T1),while 25 g of stymulan cattle/100 kg.,and200 g.of Sorbotiol /100 kg. was added to the control ration of group 2(T2)and group3(T3) ,respectively for 16 weeks and study some production traits. At end of fattening period all calves were slaughter and calculated some carcass traits. The results indicated that calves fed second ration(T2) was significantly higher(p≤0.05) in average daily gain, total gain,final weight, some body dimensions and hot and cold carcass weights than calves feed first ration (T1) and third ration (T3).While no significant effect was found of adding feed additives to the rations on most studied carcass traits and physical analysis of three ribs region. Key words:Sharabi calves, Feed Additives, production traits, carcass traits.